Fatal Tumour Lysis Syndrome Induced by Brigatinib in a Lung Adenocarcinoma Patient Treated With Sequential ALK Inhibitors: A Case Report - Wang, Yadong; Wang, Tiange; Xue, Jianchao; Jia, Ziqi; Liu, Xinyu; Li, Bowen; Li, Ji; Li, Xiaoguang; Wang, Weiwei; Bing, Zhongxing; Cao, Lei; Cao, Zhili; et al. (Frontiers in Pharmacology, 2021)
Tumour lysis syndrome (TLS) represents a group of fatal metabolic derangements resulting from the rapid breakdown of tumour cells. TLS typically occurs soon after the administration of chemotherapy in haematologic malignancies but is rarely observed in solid tumours. Here, we report a case of brigatinib-induced TLS after treatment with sequential anaplastic lymphoma kinase (ALK) inhibitors in a patient with advanced ALK-rearranged lung adenocarcinoma. The patient was treated sequentially with crizotinib, alectinib, and ensartinib. High-throughput molecular profiling after disease progression indicated that brigatinib may overcome ALK resistance mutations, so the patient was administered brigatinib as the fourth-line treatment. After 22 days of therapy, he developed oliguria, fever, and progressive dyspnoea. Clinical manifestations and laboratory findings met the diagnostic criteria for TLS. The significant decrease in the abundance of ALK mutations in plasma indicated a therapeutic response at the molecular level. Consequently, the diagnosis of brigatinib-induced TLS was established. To the best of our knowledge, this is the first case of TLS induced by sequential targeted therapy in non-small cell lung cancer. With the extensive application of sequential therapy with more potent next-generation targeted therapeutic drugs, special attention should be given to this rare but severe complication.